Seven reasons to question the hegemony of Visible Learning. Issue 1 (2nd January 2020) - McKnight, Lucinda; Whitburn, Ben
ABSTRACT: The publication of John Hattie's Visible Learning: A synthesis of over 800 meta-analyses relating to achievement in 2009 has led to the widespread adoption of the Visible Learning program around the world. Critique of this program has been less widespread, especially in English, and has tended to centre on the mechanisms of meta-analysis. We consider what Visible Learning puts to work in relation to cultural politics and find it closely aligned with agendas of neoliberalism, sexism and ableism that operate to perform exclusion in schools and to de-professionalise teachers in feminised work. We argue that the metaphor of Visible Learning itself requires much more careful attention.